2009
DOI: 10.1093/eurjhf/hfp149
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of device therapy (cardiac resynchronization therapy and implantable cardioverter defibrillator) for patients with heart failure in Europe: changes from 2004 to 2008

Abstract: AimsHeart failure (HF) patients increasingly receive device therapy, either an implantable cardioverter defibrillator (ICD) or a biventricular pacemaker, also called cardiac resynchronization therapy (CRT), or a CRT device with an ICD (CRT-D). However, epidemiological data on the use of device therapy in Europe are limited. -- Methods and results Data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 36 publications
(58 reference statements)
4
82
1
4
Order By: Relevance
“…Use of an implantable cardioverter-defibrillator was relatively infrequent, but this finding is similar to those in recent registries and trials. 24,25 The early stopping of the trial may have resulted in overestimation of the magnitude of the treatment effect, 26 but the results are consistent with those seen in RALES. 2 In conclusion, our study showed that, as compared with placebo, eplerenone added to recommended therapy for systolic heart failure in patients with mild symptoms was associated with a reduction in the rate of death from a cardiovascular cause or hospitalization for heart failure.…”
Section: Referencessupporting
confidence: 53%
“…Use of an implantable cardioverter-defibrillator was relatively infrequent, but this finding is similar to those in recent registries and trials. 24,25 The early stopping of the trial may have resulted in overestimation of the magnitude of the treatment effect, 26 but the results are consistent with those seen in RALES. 2 In conclusion, our study showed that, as compared with placebo, eplerenone added to recommended therapy for systolic heart failure in patients with mild symptoms was associated with a reduction in the rate of death from a cardiovascular cause or hospitalization for heart failure.…”
Section: Referencessupporting
confidence: 53%
“…Większość dużych prób klinicznych z zastosowaniem leków w HF przeprowadzono przed ogłoszeniem pozytywnych wyników przełomowych prób klinicznych z użyciem ICD [63,64] i CRT [313,314] (2005 r.). Dowody z tych prób klinicznych zaowocowały silnym zaleceniem tych metod w wytycznych dotyczących HF, co spowodowało ogromny wzrost częstości ich stosowania [7,315].…”
Section: Ablacja Przezcewnikowaunclassified
“…In Europe, and especially in Italy, CRT-D use is rising faster than the use of any of the other devices indicated for heart failure treatment. 13 In the light of the recent extension of European CRT recommendations to mildly symptomatic patients, 5 further growth can be expected. Recently, attention has been drawn to the number of ICD recipients who may not benefit from the device but are still exposed to procedural and device-related complications, raising the question of whether current complications of ICD therapy have been underestimated and the benefits overestimated.…”
Section: Discussionmentioning
confidence: 99%